2016
DOI: 10.14260/jemds/2016/692
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Presentations of Bronchogenic Carcinoma in a Tertiary Care Centre

Abstract: BACKGROUNDLung cancer is presently the most common malignant disease (13% of all cancers) and the leading cause of cancer deaths (19% of all cancer deaths) in the world in all age groups and in both sexes. It is the leading cause of cancer deaths in developed as well as in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…1 The result of current study demonstrated that the pathological types of bronchogenic carcinoma have changed as ADC (30.9%) has nearly equal prevalence to SCC (31.7%), followed by LCC (26.0%), while SCLC was the least prevalent type (11.4%). Similarly, several studies reported higher prevalence of SCC and ADC.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…1 The result of current study demonstrated that the pathological types of bronchogenic carcinoma have changed as ADC (30.9%) has nearly equal prevalence to SCC (31.7%), followed by LCC (26.0%), while SCLC was the least prevalent type (11.4%). Similarly, several studies reported higher prevalence of SCC and ADC.…”
Section: Discussionmentioning
confidence: 60%
“…Similar delay in presentation up to 3-4 months was reported in other studies with only 2.5 % of patients were asymptomatic. 1,3,16,21 Cough and chest were the main presenting symptoms among our patients irrespective to pathological types (p=0.8). The mechanism of cough is multifactorial as it may be due to either local growth in a centrally locating tumours (e.g.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations